Understanding the reproduction of health inequalities: physical activity, social class and Bourdieu's habitus. Issue 3 (24th March 2019) - Wiltshire, Gareth; Lee, Jessica; Williams, Oli
ABSTRACT: Health inequalities continue to exist in advanced capitalist economies and so-called lifestyle behaviours (e.g. smoking, alcohol consumption, diet and physical (in)activity) play a role in their persistence. Interventionist responses to health inequalities are often posed in terms of either individual agency or social structure – the former being criticised for its shaming/responsibilising effects and the latter for inadequately conceptualising behavioural differences within socio-economic groups. In this paper, we attempt to reconcile these two positions by drawing on Bourdieu's concept of habitus, arguing that health enhancing behaviours are better understood as practices constrained and enabled within social class contexts. As many interventionist health policies target young people in schools, we take the example of physical education and youth sport to illustrate how young people's dispositions towards health practices are part of an emerging class habitus. We draw on data from a sociological study of young people's physical activity and health in which twenty-nine participants (aged 13–14) from four socio-economically diverse school settings took part. The data presented here are selected from 60 focus group transcripts, ethnographic fieldnotes from 6 months of school visits and visual data from participants. Our data indicate that class differences exist in both the kinds of activities practiced by pupils and ways in which they are practiced. We argue that class-based differences are, at least partially, matters of embodied inclinations and dispositions that are already evident at the age of 13/14. Consequently, we demonstrate how school-focused health promotion through physical education and youth sport may contribute to health inequalities as a result of being more or less accessible and appealing to pupils with a different classed-habitus within different educational fields. This paper questions the on-going interventionist policies that position schools as sites for health promotion without adequately accounting for the influence of class cultures.